2022
DOI: 10.1097/aog.0000000000004847
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Inhaled Nitric Oxide for the Treatment of Spontaneously Breathing Pregnant Patients With Severe Coronavirus Disease 2019 (COVID-19) Pneumonia

Abstract: High-dose inhaled nitric oxide was associated with shorter time on supplemental oxygen and shorter intensive care unit and hospital length of stay for pregnant patients with severe coronavirus disease 2019 (COVID-19) pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
(82 reference statements)
0
11
0
3
Order By: Relevance
“…In addition to its effects on pulmonary function, the inhalation of NO also exhibits antiviral and anti-inflammatory properties, including the inhibition of neutrophil adhesion and the release of proinflammatory cytokines 69. Although the concentrations of inhaled NO required for antimicrobial effects remain unknown, previous studies have shown that up to 300 ppm of inhaled NO is safe and well tolerated in patients with viral pneumonia, such as COVID-1951 52 and respiratory syncytial virus pneumonia 70…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its effects on pulmonary function, the inhalation of NO also exhibits antiviral and anti-inflammatory properties, including the inhibition of neutrophil adhesion and the release of proinflammatory cytokines 69. Although the concentrations of inhaled NO required for antimicrobial effects remain unknown, previous studies have shown that up to 300 ppm of inhaled NO is safe and well tolerated in patients with viral pneumonia, such as COVID-1951 52 and respiratory syncytial virus pneumonia 70…”
Section: Discussionmentioning
confidence: 99%
“…It also significantly shortens the conversion time in positive patients (p=0.044) and improves the conversion rate at 7 days after treatment (82.8% vs control 66.7%, p=0.046) 48. Despite its theoretical plausibility and potential, the clinical evidence supporting the efficacy of NO in treating COVID-19-related pulmonary complications has primarily originated from observational studies49 50 or small trials,51 yielding inconsistent reported results. Recently, a phase II study demonstrated an improvement of PaO 2 /fraction of inspired oxygen (FIO 2 ) with high-dose NO (at 80 ppm) at 48 hours compared with usual care in adults with acute hypoxaemic respiratory failure due to COVID-19 52.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study evaluated the use of high-dose inhaled nitric oxide for pregnant women with severe COVID-19 pneumonia [ 67 ]. Inhaled nitric oxide was associated with more oxygen supplementation-free days, and shorter length of stay in intensive care and in hospital, and did not increase adverse maternal and neonatal outcomes.…”
Section: Special Populationsmentioning
confidence: 99%
“…Pregnant patients are at risk of developing AHRF due to pregnancy. A recent cohort study reported that iNO was associated with a reduced need for oxygen supplementation and a shorter hospital stay for pregnant patients with COVID-19 pneumonia in the absence of adverse events in mothers or infants [ 29 ], supporting the safety of iNO therapy. Although there have yet to be active debates on the effect of iNO on the clinical outcomes of COVID-19 patients [ 30 , 31 ], a number of studies have confirmed that iNO therapy is associated with improved oxygenation parameters in COVID-19 patients [ 5 , 21 , 32 ].…”
Section: No Therapy For Covid-19 Patientsmentioning
confidence: 99%